Dye-Sensitized Solar Cells (Dssc) Using Natural Dyes Extracted From Red Cabbage And Counter Electrode Based Tio2-Graphite Composites - Haryati, Tanti; Mulyono, Tri; Oktavianawati, Ika; Badrianto, Wawan (UNEJ e-Proceeding, 2014)
Dye sensitized solar cells (DSSC) has been a popular research topic which benefits in high energy conversion efficiency and less cost in fabrication process. The components of DSSC consist of photoanode, electrolyte, and counter electrode that are arranged as sandwich. The photoanode contains ITO (indium tin oxide) glass covered by TiO2 particles, while the counter electrode contains ITO glass covered by composite of TiO2-graphite as counter electrode and red cabbage extract, as a dye agent. The cell was fabricated in various amount of graphite, i.e 10%; 30%; and 50 %, and time of soaking i.e 2; 13; 24; and 48 hours. The performance of the solar cell per active area of ââ1 cm2 was tested on irradiation of 75 Watt halogen lamp (distance 15 cm) and measured by multimeter and rheostat. The optimum synthesis condition of DSSC was obtained with composition of TiO2:graphite on the counter electrode is 70%:30 %, and soaking time in dye agent is for 24 hours. This cell results in an optimum performance, Isc = 0.028 mA ;Voc = 0.344 mV, FF = 0.29 and = 0.0055 % efficiency. Keywords: DSSC, Red Cabbage, Counter Electrode